软弱黄土隧道支护结构力学特性测试 = Mechanical characteristic test of tunnel support structure in weak loess stratum - 赖金星 Lai Jin-xing (2020)
为研究软弱黄土隧道支护结构的受力特性，优化黄土隧道设计理论，以西宁过境高速公路某黄土隧道为依托，选取杂填土段、深埋段和浅埋段进行了大规模的现场测试，从支护受力的空间分布、时间分布、计算方法以及对比验证等方面，对围岩与初支接触压力、初支与二衬接触压力及二衬和仰拱混凝土的应变进行了系统的研究。分析结果表明：拱顶、拱肩处的压力值较大，是黄土隧道最危险的部位，容易发生坍塌；围岩压力计算值与实测值相差较大，现有方法在计算黄土断面围岩压力时存在较大的误差；深埋段围岩压力稳定时间最短，浅埋段次之，杂填土段时间最长；软弱黄土隧道“新奥法”原理指导下，“强初支，弱二衬”设计理念的采用，使二衬荷载承担比例控制在11%~36%范围内，充分发挥了初支对围岩变形的抑制作用，二衬仍作为安全储备. In order to analyze the mechanical characteristics of tunnel support structure in weak loess stratum and optimize the design theory of loess tunnel, large scale field tests of the sections of miscellaneous fill, deep depth and shallow depth were conducted for a loess tunnel of the highway through Xining City. In the aspects of space distribution, time distribution, calculation method and contrast verification, the contact pressure between surrounding rock and primary liner, the contact pressure between primary liner and secondary liner, and the strains of secondary liner and inverted arch were systematically studied. Analysis result shows that the vault and spandrel are the most dangerous parts of loess tunnel for their large pressures and prone to collapse. The calculated values of surrounding rock pressure are very different from the measured values, and the existing method has a big error in the calculation of surrounding rock pressure at the loess section. The time for surrounding rock pressure to stabilize is shorter at deep depth section than the value at shallow depth section, and the time at the section of miscellaneous fill is the longest. Following the guidance of New Austrian Tunnelling Method for the loess tunnel and the design concept of “strong primary liner and weak secondary liner”, the loading proportions of the secondary liner have been kept in the range of 11%-36% and the primary liner has played an important role in controlling the deformation of surrounding rock. The secondary liner has played as safety reserve.